2018
DOI: 10.3233/rnn-170733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combining high- and low-frequency repetitive transcranial magnetic stimulation on upper limb hemiparesis in the early phase of stroke

Abstract: The results indicated that both LF- and LF-HF rTMS were effective in promoting upper limb motor recovery in patients with acute stroke. Combining HF- and LF-rTMS protocol in the present study is tolerable and more beneficial for motor improvement than the unilateral use of LF-rTMS alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 27 publications
3
47
0
2
Order By: Relevance
“…Compared with a single intervention, a combination approach of different techniques has been proven to be better for alleviating movement disorder (2). Lots of trials have shown that movement function improvement after stroke can be enhanced by non-invasive brain stimulation techniques combined with conventional clinical practice (36).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a single intervention, a combination approach of different techniques has been proven to be better for alleviating movement disorder (2). Lots of trials have shown that movement function improvement after stroke can be enhanced by non-invasive brain stimulation techniques combined with conventional clinical practice (36).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that low-frequency rTMS to the contralesional hemisphere combined with high-frequency rTMS to the lesional hemisphere was efficacious in accelerating upper limb motor recovery in patients with acute stroke. In particular, the combination of different-frequencies rTMS was more beneficial for motor improvement than the low-frequency rTMS use only (Long et al, 2018). Herein, we found that rTMS of 1, 10, and 20 Hz significantly increased NSPC proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 60%
“…Investigators should focus on addressing the question of how to design stimulation methods to maximize the rehabilitation benefits of HF-rTMS. In the acute stage, inhibitory stimulation of the unaffected contralesional hemisphere is more effective than excitatory stimulation of the affected contralesional hemisphere [35]. Moreover, whether effects between inhibitory low-frequency stimulation and combined low-frequency and high-frequency stimulations on the uninjured side of the brain differ remains to be elucidated.…”
Section: Rtms On Motor-function Recovery After Acute Strokementioning
confidence: 99%